Selenium and Selenoproteins at the Intersection of Type 2 Diabetes and Thyroid Pathophysiology - Francesca Gorini; Cristina Vassalle (MDPI AG, 2022)
Type 2 diabetes (T2D) is considered one of the largest global public-health concerns, affecting approximately more than 400 million individuals worldwide. The pathogenesis of T2D is very complex and, among the modifiable risk factors, selenium (Se) has recently emerged as a determinant of T2D pathogenesis and progression. Selenium is considered an essential element with antioxidant properties, and is incorporated into the selenoproteins involved in the antioxidant response. Furthermore, deiodinases, the enzymes responsible for homeostasis and for controlling the activity of thyroid hormones (THs), contain Se. Given the crucial action of oxidative stress in the onset of insulin resistance (IR) and T2D, and the close connection between THs and glucose metabolism, Se may be involved in these fundamental relationships; it may cover a dual role, both as a protective factor and as a risk factor of T2D, depending on its basal plasma concentration and the individual's diet intake. In this review we discuss the current evidence (from experimental, observational and randomized clinical studies) on how Se is associated with the occurrence of T2D and its influence on the relationship between thyroid pathophysiology, IR and T2D.